NAHosMIP experimental protocol ... - Jackson, Laura; Alastue de Asenjo, Eduardo; Bellomo, Katinka; Danabasoglu, Gokhan; Hu, Aixue; Jungclaus, Johann; Lee, Warren; Meccia, Virna; Saenko, Oleg; Shao, Andrew; Swingedouw, Didier (Zenodo, 2022)
This package contains details of the experimental protocol for the North Atlantic Hosing Model Intercomparison Project (NAHosMIP). See https://www.tipes.dk/na-hosing-mip/ The experimental protocol is described in detail in Jackson et al, (2022), Understanding AMOC stability: the North Atlantic Hosing Model Intercomparison Project. GMD [Full reference to come] The files attached are: create_hosing_GC3LL.py - python code to create a netcdf file with uniform hosing of a given rate (ie 0.3 Sv). This file is set up to read in grid data for HadGEM3-GC3-1LL create_hosing_GC3LL_grl_v2.py - python code to create a netcdf file with hosing around Greenland of a given rate (ie 0.1 Sv). This file is set up to read in grid data for HadGEM3-GC3-1LL and has some grid locations that are specific to the model. hosing.nc - example of uniform hosing of 0.3Sv for HadGEM3-GC3-1LL grid hosing_grl.nc - example of hosing around Greenland of 0.1Sv for HadGEM3-GC3-1LL grid check_hosing_GC31LL.py - script to check hosing file and code ...